How Does Any One Film Explore Moral Problems Associated with Choice? - Xinye Song (Art and Society, 2024)
The Dark Knight (Christopher Nolan, 2008) focuses on Batman Bruce Wayne (Christian Bale): the dark knight, and Harvey Dent (Aaron Eckhart): the white knight as Gotham’s prosecutor, who work together to fight the criminal Joker (Heath Ledger). Harvey Dent was a prosecutor who defended the law, upheld justice, and put many criminal organizations in prison in Gotham. But in the process of confronting the Joker, Harvey Dent gradually became “Two-Face” who committed multiple murders. This ultimately left Batman with a difficult choice: whether to reveal the crimes committed by Harvey Dent and therefore release all the prisoners that led to Harvey’s arrest, or to take all the crimes upon Batman himself and disappear from Gotham, leaving the legal system established by Harvey Dent to continue to work in Gotham. Although Batman ultimately chose to take the blame for Harvey’s crimes, perpetuating the legal system established by Harvey Dent, and making Batman’s identity disappear as a result. However, Batman’s choice still raises many moral problems. Moral problems are related to the rights and wrongs of our actions, and how to distinguish morally right and morally wrong is “the primary question posed within ethics” (Karofsky & Litch, 1963, p. 145), in other words, moral philosophy is ethics. According to Downing and Saxton, “Ethics [ …] is a process of questioning” and “designates a way of responding to the encounter between the self and others” (Downing & Saxton, 2010, p. 3), this illustrates that a question about ethics is approached from different people or different perspectives. This also dictates that when it comes to an action as morally right or wrong, it must be approached from a different perspective. At the same time, “Film as a medium of “ethical experience: through which conflicting, clashing, or incompatible ideas, commitments, or beliefs can be revealed” (Sinnerbrink, 2016, p. 6). This explains that film, as a medium for the display of behaviour, can reveal the different characteristics present in the act, providing a space for the viewer to make a moral judgement. Therefore, this essay will base on Amy Karofsky and Mary M. Litch’s categorical discussion of ethics, specifically analysing the moral problems associated with Bruce Wayne’s choices at the end of The Dark Knight.